Madagascar : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1995)
This paper describes the economic developments in Madagascar during the 1990s. In early 1994, the authorities prepared a medium-term policy statement with an outward orientation. Accordingly, a sweeping reform of the exchange and trade system was implemented in May 1994, including the floating of the Malagasy franc. However, financial policy was not sufficiently supportive: ad hoc tax exemptions were granted, particularly to foodstuffs and petroleum products, and other taxes were not fully collected. Thus, the fiscal deficit deteriorated, leading to a sharp acceleration in money creation and inflation, which rose to 61 percent by end-1994.